Survey of mobile object tracking protocols in wireless sensor networks: a network–centric perspective. (1st October 2012) - Naderan, Marjan; Dehghan, Mehdi; Pedram, Hossein; Hakami, Vesal
Mobile object tracking in Wireless Sensor Networks (WSNs) has gained much attention during recent years owing to its growing application potential for the ubiquitous society. In this paper, we present an investigation and taxonomy of the state–of–the–art in tracking moving objects in WSNs. To this end, we define the target tracking problem in general and introduce the major design considerations for an efficient Object Tracking Sensor Network (OTSN) in particular. We typify a complete object tracking solution as a system of signal processing–based algorithms in charge of target identification/classification and network–centric protocols as the communication substrate. Our special highlight would be on the discussion of the network–centric protocols built around the notion of OTSN. We outline the advantages as well as the performance issues in relevant schemes and conduct a brief comparative study. The survey concludes with several key open problems together with a summary of directions for future works.